Prevalence of Apical Periodontitis and Its Associated Factors in Endodontically Treated Teeth: A CBCT Study - Bahar Asheghi; Sayedeh Zahra Khosravanii; Maryam Zangoie Booshehri; Milad Zanjani; Golshan Mohammadi (Isfahan University of Medical Sciences, 2023)
The aim of this study wastoinvestigate the prevalence of apical periodontitis and some associated factors in endodonticallytreated teeth among an Iranian population using Cone-Beam Computed Tomography (CBCT).Materials & Methods:In this cross-sectional study, 470 CBCT scans (including 1287 root-filled teeth) were randomly selected from patients referred to a maxillofacial radiology center in Shiraz. Iran, during 2017-2020. Cone-Beam Computed Tomography Periapical Index (CBCTPAI) was used to assess the presence of apical periodontitis. In root-filled teeth with apical periodontitis, the length of the root filling and the presence of missed canals were investigated. Chi-square analysis was used to assess the relationship between apical periodontitis, age, gender of the patients, tooth type, and tooth location. A p value < 0.05 was considered significant.Results:Apical periodontitis was observed in 23.5% of the root-filled teeth. The prevalence of apical periodontitis in males (26.3%) was significantly higher than females (21.2%) (p value = 0.035). Also, the prevalence of apical periodontitis in root-filled teeth in patients under 50 years old (26.2%) was significantly higher than patients over 50 years old (20.3%) (p value = 0.012).The most common teeth with apical periodontitis were maxillary and mandibular first molars. Among the root-filled teeth with apical periodontitis, under-filling, over-filling and missed canals were observed in 37.6%, 16.2% and 13.9% of cases, respectively.Conclusion:The prevalence of apical periodontitis in root-treated teeth is relatively high (23.5%). Patients' age, gender, and type of tooth are among the factors that affect the prevalence of apical periodontitis in endodontically treated teeth